Predicting success in junior elite basketball players--the contribution of anthropometic and physiological attributes - Hoare, D. G. (Journal of Science and Medicine in Sport, 2000)
Talent identification programs have traditionally focused on individual sports with discrete physical and physiological characteristics. Limited attention has been directed toward predicting performance in team sports. This study measured anthropometric and physiological attributes of 125 male and 123 female junior basketball players competing at the Australian Under 16 championships in 1998. In addition, experienced coaches rated the performance of players during the championships. Performance profiles were compared across playing positions and by playing performance ('Best versus Rest'). Differences in anthropometric characteristics were present across some playing positions for both males and females. Speed and agility differences between some playing positions were also present. Best players differed to Rest players on a number of anthropometric and physiological variables for both males and females. Regression analyses indicated the test variables accounted for a significant proportion of variance in playing performance for both females (41.3%) and males (38.3%). A Z score analysis indicated good alignment between the test and coach ranking of the Best player in four out of five positions for females and two out of five positions for males. Anthropometric and physiological profiling can contribute to selection procedures in junior basketball, however determinants of success are multi-factorial.